The Public Space as Backbone for Social Integration and as the Scenario of Civic Life - Santos De Aguirre, María del Rosario; Pimiento Osorio, Juan (DIXI, 2015)
Introduction: Thnks to the 1991 Political Constitution of Colombia, the public space has been re-examined from the legal perspective. At the same time, erritorial administrations, such as Bucaramanga, have created public policies for its recognition, protection and recovery. Nonetheless, actions by local administrators have not been guided by fully constitutional criteria, nor are they based on evaluation of the collective prerogative that is superior to its material aspect. Methodology: Th proposal stems from a careful study of legal provisions that regulate the public space, contrasted with its valuation in civic education trends from the public perspective and that of urbanism, as a broad basis. Thn, using surveys, the set of ideas about the public space applied by basic actors in its use in the municipality of Bucaramanga is recognized. Ths signifid interlocution with the administrative authority to recognize public policy in the matter and reach a consensus in academia that would include a critique of the work carried out while facilitating valuation of the public space from a new perspective. Results and Conclusions: Given the above, academia, represented by the Law Faculty of the Universidad Pontifiia Bolivariana, proposes a broader vision of the public space, in which there are supralegal aspects that are in harmony with social perception about that right and which also are respectful of, and have a constitutionalism with, human features.